Substrate recognition of holocytochrome c synthase: N‐terminal region and CXXCH motif of mitochondrial cytochrome c. Issue 18 (30th July 2014) - Zhang, Yulin; Stevens, Julie M.; Ferguson, Stuart J.
Abstract : Holocytochrome c synthase (HCCS) attaches heme covalently to mitochondrial respiratory cytochromes c . Little is known about the reaction of heme attachment to apocytochromes c by HCCS, although recently it has been established that the CXXCH motif and the N‐terminus of the apocytochrome polypeptide are important protein–protein recognition motifs. Here, we explore further the important features of the N‐terminal sequence and investigate what variations in the CXXCH residues are productively recognised by HCCS in its substrate. Abstract : Holocytochrome c synthase (HCCS) does not attach heme to cytochromes lacking the histidine in the CXXCH motif. HCCS can recognise C‐terminally truncated cytochromes c . The aromatic nature of, or possibly shape complementarity to, F15 in cytochrome c is important for recognition by HCCS. The spacing of the phenylalanine relative to the CXXCH is a recognition feature.